The Adapted Firesetting Assessment Scale: reliability and validity. Issue 7 (27th May 2022) - Collins, J.; Langdon, P. E.; Barnoux, M.
Abstract: Background: The Adapted Firesetting Assessment Scale was developed for use with adults with developmental disabilities targeting fire‐related factors thought to be associated with deliberate firesetting behaviour (i.e. attitudes towards fire, fire interest, fire normalisation, identification with fire and fire safety awareness). However, the psychometric properties of the scale are yet to be evaluated. Method: The reliability, validity, comprehensibility, relevance and comprehensiveness of the Adapted Firesetting Assessment Scale were evaluated. Fifty‐nine adults with developmental disabilities, some of whom had a history of firesetting, completed the Adapted Firesetting Assessment Scale on two occasions. Feedback about the questionnaire was sought from both participants and professionals. Results: The AFAS has acceptable internal consistency and excellent test–retest reliability. The attitudes towards fire, fire normalisation, poor fire safety subscales and total scores discriminated firesetters from non‐firesetters. Content analysis of feedback indicated items of the AFAS were understood, relevant, accessible and comprehensible. Conclusion: A larger study is needed to examine the factor structure of the AFAS.